2018
DOI: 10.1111/tops.12360
|View full text |Cite
|
Sign up to set email alerts
|

Honesty Speaks a Second Language

Abstract: Theories of dishonest behavior implicitly assume language independence. Here, we investigated this assumption by comparing lying by people using a foreign language versus their native tongue. Participants rolled a die and were paid according to the outcome they reported. Because the outcome was private, they could lie to inflate their profit without risk of repercussions. Participants performed the task either in their native language or in a foreign language. With native speakers of Hebrew, Korean, Spanish, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…Foreign-language manipulations ( k = 11) were included because recent evidence suggests that completing a study in one’s native language (vs. in a foreign language) can induce an intuitive mind-set (Bereby-Meyer et al, 2018; Geipel, Hadjichristidis, & Surian, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreign-language manipulations ( k = 11) were included because recent evidence suggests that completing a study in one’s native language (vs. in a foreign language) can induce an intuitive mind-set (Bereby-Meyer et al, 2018; Geipel, Hadjichristidis, & Surian, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…For example, correlational studies have revealed that impulsivity—the tendency to decide intuitively—is positively associated with academic cheating (Anderman, Cupp, & Lane, 2009) and that when people are drained of the cognitive resources required for deliberation they are more likely to engage in workplace deviance (Christian & Ellis, 2011) and unethical behavior (Barnes, Schaubroeck, Huth, & Ghumman, 2011). Experimental work has similarly revealed that restraining participants’ deliberate thinking through cognitive load (e.g., Welsh & Ordonez, 2014), time pressure (Shalvi, Eldar, & Bereby-Meyer, 2012), mental or physical depletion (e.g., Kouchaki & Smith, 2014), priming of intuition concepts (e.g., Zhong, 2011), or conducting experiments in a native language (vs. a foreign language; Bereby-Meyer et al, 2018) increases self-serving dishonesty. Together, these findings suggest the following: Dishonesty is intuitive.…”
Section: Intuitive Dishonesty?mentioning
confidence: 99%
“…As can be seen in Fig 3, the likelihood to engage in future deals was slightly lower for requesting (Mean = 4.97, SD = 1.0, 95% CL [4.68, 5.26]) than for demanding a discount (Mean = 5.1, SD = 3.8, 95% CL [4.84, 5.41]). Thus, unlike in Study 1 and 2, H1b was not supported, suggesting that foreign language had a weaker effect on behavior relative to native language [82].…”
Section: Resultsmentioning
confidence: 99%
“…Another positive effect of foreign language use was found in the domain of self-regulation. People tend to order healthier deserts in a restaurant (Klesse et al 2015) and are less willing to lie in a foreign language (Bereby-Meyer et al 2017).…”
Section: Foreign Language Effectmentioning
confidence: 99%